Efektivitas Pengelolaan Barang Publik dalam Meningkatkan Kualitas Pelayanan Publik di Indonesia - Fadila Putri; Fatimah Hafni Simanjuntak; Nadra Syahira Putri; Ahmad Wahyudi Zein (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2025)
this study aims to analyze the effectiveness of the management of public goods in improving the quality of public services in Indonesia. Public goods have nonrivalry and nonexcludability characteristics, which means it can be used by many people simultaneously without reducing mutual benefits, and cannot exclude anyone from its use. This study uses a qualitative descriptive method with a literature study approach, reviewing economic theories and public policies and national regulations related to public services. The results showed that good public goods management, such as infrastructure and basic services provided by the state, contributed directly to the effectiveness and quality of services to the community. However, there are still challenges in the form of limited resources, lack of supervision, and not optimal utilization of public assets. Therefore, increasing governance and strengthening of regulations is crucial in realizing equitable, quality and sustainable public services.